The Control of Greenhouses Based on Fuzzy Logic Using Wireless Sensor Networks - Alpay, Ozlem; Erdem, Ebubekir (Atlantis Press, 2019)
Greenhouses cannot be easily controlled because their climate parameters are interrelated. This study contributes to increasing the quality and yield of greenhouses by saving time, energy, light and water consumption via measuring and controlling the climate parameters that are effective in forming climate factors in greenhouses. The greenhouse climate variables including temperature, relative humidity, soil moisture and light intensity were measured by a realistic sensor application. In this way, several sensor nodes, that belong to the nodal packages were distributed to a wireless sensor network (WSN) constructed in a star topology. In addition, the data obtained from the nodes, have been controlled and monitored with the fuzzy logic-based control strategy proposed as a developing, smart and remotely accessible Android-based interface. The proposed method has been analyzed, and its performances have been evaluated in terms of the benefits of both the user and the greenhouse. (c) 2019 The Authors. Published by Atlantis Press SARL.
Keywords: Wireless sensor network; Fuzzy logic; Internet of things; Smart greenhouse; Greenhouse climate control